Effect of long-term serum sodium levels on the prognosis of patients on maintenance hemodialysis - Siyu Chen; Bin Pan; Xiaowei Lou; Jianghua Chen; Ping Zhang (Renal Failure)
Abnormal serum Na (SNa) levels are common in patients with chronic kidney disease (CKD) which is associated with increased morbidity and mortality. There are relatively few studies on the effect of SNa indicators on the prognosis of patients undergoing maintenance hemodialysis (MHD). We aim to investigate the effect of long-term SNa levels on the survival and prognosis of patients undergoing hemodialysis (HD). Newly entered HD patients in the registration system of Zhejiang Provincial Dialysis Quality Control Center between January 1, 2010 and December 31, 2019 were included and followed up until December 31, 2020. Multiple sodium levels were collected from patients, defining long-term SNa as the mean of multiple SNa, according to which patients were grouped, with the prognostic differences between subgroups compared by Kaplan-Meier modeling and multifactorial Cox regression modeling. Finally, a total of 21,701 patients were included in this study and Cox regression showed that decreased SNa levels (Na < 135 mmol/L, HR = 1.704, 95% CI 1.408–2.063, p < 0.001; 135≦Na≦137.5 mmol/L, HR = 1.127,95% CI 1.016–1.250, p = 0.024) and elevated SNa levels (142.5 < Na≦145mmol/L, HR = 1.198, 95% CI 1.063–1.350, p = 0.003; Na > 145mmol/L, HR = 2.150, 95% CI 1.615–2.863, p < 0.001) were all independent risk factors for all-cause mortality in MHD patients.